Hyperoxia and Delayed Cerebral Vasospasm in Aneurysmal Subarachnoid Hemorrhage. (16th November 2020) - Reynolds, Rebecca; Amin, Shaunak; Jonathan, Sumeeth V; Tang, Alan R; Lan, Matthews; Bastarache, Julie; Ware, Lorraine; Thompson, Reid C
Abstract: INTRODUCTION: Cerebral vasospasm is a major contributor to disability and mortality after aneurysmal subarachnoid hemorrhage (aSAH). Oxidation of cell-free hemoglobin plays an integral role in neuroinflammation and is a suggested source of tissue injury after aneurysm rupture. METHODS: This single-center retrospective cohort study included adult patients who presented with an ICD-9/10 diagnosis of aSAH from 2007–2017. Patients without intracranial imaging, arterial PaO2 values, or who died within 96 hours post-rupture were excluded. The degree of hyperoxia was defined by the highest PaO2 measured within 72 hours after aneurysmal rupture. The primary outcome was delayed cerebral vasospasm, which included asymptomatic cases and delayed cerebral ischemia (DCI). Mortality was a secondary outcome. RESULTS: 345 patients met inclusion criteria; 218 patients (63%) developed vasospasm. Of those that developed vasospasm, 85 were diagnosed with DCI (39%). The average patient age was 55 ± 13 years, and 68% were female. Ninety percent presented with Fisher Grade 3 or 4 hemorrhage (N = 310) while 42% presented as Hunt-Hess Grade 4 or 5 (N = 146). Vasospasm included both DCI and asymptomatic cases as there was no statistically significant predictor distinguishing these two groups, including no difference in maximum PaO2. In univariable analysis, patients exposed to higher levels of PaO2 by quintile of exposure died and developed vasospasm in a dose-dependent fashion ( P = . 015 and P = . 019, respectively). In multivariable analysis, early hyperoxia was independently associated with vasospasm (OR = 1.15 per 50 mmHg increase in PaO2 [1.03, 1.28]; P = . 013), but not mortality (OR = 1.10 [0.96, 1.25]; P = . 173) following aSAH. CONCLUSION: Hyperoxia within 72 hours post-aneurysmal rupture is an independent predictor of cerebral vasospasm, but not mortality in subarachnoid hemorrhage. Hyperoxia may represent a modifiable risk factor for vasospasm.